2013
DOI: 10.1179/1743294412y.0000000072
|View full text |Cite
|
Sign up to set email alerts
|

Si doped ZnO thin films for transparent conducting oxides

Abstract: Transparent conductive silicon doped zinc oxide (SZO, 3%Si) thin films are grown by direct current magnetron sputtering on glass substrates at room temperature. Experimental results show that the sputtering time has a significance impact on the growth rate, crystal quality and electrical properties of the films, and have little impact on the optical properties of the films. The growth rate decreases with the sputtering time. The resistivity of ZnO/Si films decreases as the sputtering time increases from 8 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the high substrate preparation temperature makes the preparation conditions higher and more difficult, which is contrary to our desire to obtain better quality at low cost. [26][27][28][29][30][31][32][33][34]…”
Section: Introductionmentioning
confidence: 99%
“…However, the high substrate preparation temperature makes the preparation conditions higher and more difficult, which is contrary to our desire to obtain better quality at low cost. [26][27][28][29][30][31][32][33][34]…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity of transparent conducting films (e.g. In 2 O 3 , ZnO, and SnO 2 ) can be increased by introducing a suitable concentration of oxygen vacancies and/or dopants to increase the carrier density and conductivity [24,25]. Thus, the low resistivity of the deficient oxides in this study may be attributed to the high concentration of oxygen vacancies and incorporation of some dopants (Fe +3 , Co +3 , Ni +2 , Ti +4 or Si +4 ), which could increase the free electron carrier concentration for conduction.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many deposition techniques have been proposed to prepare ZnO films, for instance, magnetron sputtering, 11-15 molecular beam epitaxy, chemical vapour deposition, spray pyrolysis, pulsed laser deposition, sol-gel process and so on. 16-18 Compared with the other techniques, magnetron sputtering has relatively high deposition rate, low substrate temperature, high film thickness uniformity, good controllability and high repeatability; 15 so it is a preferable method for film preparation and has been widely applied in industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…16-18 Compared with the other techniques, magnetron sputtering has relatively high deposition rate, low substrate temperature, high film thickness uniformity, good controllability and high repeatability; 15 so it is a preferable method for film preparation and has been widely applied in industrial production. And it was reported that the processing conditions would significantly affect the quality of ZnO films, such as sputtering atmosphere and gas pressure, 11 substrate temperature, 12 sputtering power, 13 deposition time, 14 and annealing. 15 Therefore, one of the key topics for the preparation of ZnO thin films through magnetron sputtering is to understand the effect of processing parameters on the composition, structure and properties of the films.…”
Section: Introductionmentioning
confidence: 99%